Akibat Hukum Peredaran Informasi yang Tidak Sesuai Pada Kemasan Produk Makanan - Putu Gede Prema Sena; Anak Agung Sagung Laksmi Dewi; Ni Made Puspasutari Ujianti (Jurnal Analogi Hukum, 2022)
Lately, there is information on food packaging that has been widely spread among the public that does not match or is incorrect the information contained on the packaging of food products. In this study there are two formulations of the problem, namely how to enforce criminal law for perpetrators and legal protection for consumers against the circulation of products that do not match the information on packaging. This thesis uses normative legal research with a statutory approach, a conceptual approach, and a case approach. The results of this discussion explain that business actors who distribute products that do not comply with packaging information may be subject to criminal law contained in Article 19 paragraph 4 and Article 62 UUPK, and also explains legal protection for consumers which is divided into two, namely legal protection. Preventive measures that focus on prevention efforts, one of which is providing a legal umbrella for consumers and are repressive in the form of enforcement efforts such as giving sanctions to perpetrators. This study is that there should be countermeasures from the government in the form of inspections and also the community as consumers must be critical and careful about the food products they buy.